Analysis of Figurative Language in Anne Marie Songs - Pandji, Nur' Ain; Lihawa, Kartin; Bouti, Suleman; Fatsah, Hassanuddin; Danial, Haris (Sekolah Tinggi Agama Islam Kuningan, 2025)
This research investigates the types and meanings of figurative language in Anne-Marie’s songs Trainwreck and Kills Me to Love You. Figurative language plays a significant role in enriching lyrical content by conveying deeper emotional and symbolic meanings. The theoretical framework is based on Hurford et al. (2007) and Lord (1855), who classify figurative language into nine categories: metaphor, hyperbole, personification, idiom, metonymy, synecdoche, hypocrisy, apostrophe, and allegory. The findings reveal that only four types metaphor, hyperbole, personification, and idiom appear in the selected songs. Metaphor and hyperbole emerged as the most dominant, emphasizing emotional intensity and psychological depth. This research adopts a qualitative descriptive approach using library research to analyze the figurative expressions in the lyrics. The analysis shows that figurative language in Anne-Marie’s songs illustrates themes of toxic relationships, heartbreak, and emotional resilience. Expressions such as “I’m a trainwreck” and “It kills me to love you” demonstrate how figurative language is used to portray emotional turmoil and relational conflict in a relatable and poetic manner.